ChemInform Abstract: Dual Gold Catalysis: A Novel Synthesis of Bicyclic and Tricyclic Pyrroles from N‐Propargyl Ynamides. Issue 26 (June 2015) - Tokimizu, Yusuke; Wieteck, Marcel; Rudolph, Matthias; Oishi, Shinya; Fujii, Nobutaka; Hashmi, A. Stephen K.; Ohno, Hiroaki
Abstract In the title synthesis, the gold catalyst not only activates the C—H bond to form a gold vinylidene complex, but also activates the alkyne group of ynamide by coordination.